Relationship between Lifestyle habits and the Indian Diabetes Risk Score in a community based study at Meerut - Kaur, Amandeep; Bansal, Rahul; Parashar, Pawan; Chaudhary, Varsha; Pant, Bhawana; Nasser, Kaynat (Indian Journal of Community Health, 2025)
Introduction: Diabetes mellitus, particularly Type 2 Diabetes Mellitus (T2DM), is a rapidly growing global health concern, with India facing a diabetes epidemic. The Indian Diabetes Risk Score (IDRS) is an effective tool for identifying individuals at risk of undiagnosed T2DM by considering factors such as age, abdominal obesity, family history, and physical activity. Lifestyle factors, including diet, screen time, sleep, and stress, are significant contributors to the development of T2DM, making the study of these factors essential for effective prevention strategies. Aim & Objective(s): The study aims to estimate the proportion of the population under different risk categories of IDRS and explore the association between various lifestyle habits and high-risk IDRS scores. Methodology: A community-based cross-sectional study was conducted in Multan Nagar, Meerut, from September 2022 to August 2023. A sample size of 503 individuals aged 30 and above was selected using a two-stage sampling technique. Data on socio-demographics, family history, dietary habits, physical activity, screen time, addiction history, and stress levels were collected using a pre-tested questionnaire. Chi-square tests were used to analyze the associations, with a p-value < 0.05 considered statistically significant. Results: The study found that 53.1% of participants were classified as moderate risk, 35.38% as high risk, and 11.53% as low risk based on their IDRS scores. High screen time and shorter sleep duration were significantly associated with higher IDRS scores (p-value < 0.00001). No significant association was found between dietary habits and high-risk IDRS scores. Discussion: Lifestyle factors such as screen time and sleep duration were significantly linked to diabetes risk, aligning with findings from previous studies. Increased screen time and insufficient sleep were associated with a higher risk of T2DM. However, dietary habits did not exhibit a significant correlation with the IDRS, suggesting that other factors may play a more substantial role in the risk of diabetes. Conclusion: This study highlights the significant impact of screen time and sleep duration on the Indian Diabetes Risk Score, suggesting the need for interventions targeting these modifiable lifestyle factors to prevent T2DM. While dietary habits did not show a significant relationship with the risk score, further research is needed to explore other contributing factors.